The Effect Of Leadership Style And Work Discipline On Employee Performance In The Production Division Of PT Wonokoyo Jaya Kusuma In Cikande Serang-Banten - Handayani, Heni; Sartika, Dewi (Pascasarjana Universitas Pasundan, 2025)
The purpose of this study was to find the effect of Leadership Style and Work Discipline on Employee Performance at PT Wonokoyo Jaya Kusuma, both partially and simultaneously. The method used is a quantitative method. The sampling technique used is saturated sampling using a sample of 60 respondents. Data analysis using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are that leadership style has a significant effect on employee performance based on the hypothesis test obtained with T count> T table (6.810> 1.672), ? value <Sig.0.05 or (0.000 <0.05) which means H0 is rejected and H1 is accepted and the regression equation value Y = 14.538 + 0.391 X1, the coefficient value obtained is 0.667 meaning that both variables have a positive relationship level. The determination value or contribution of its influence is 0.435 or 43.5%. Work discipline has a significant effect on employee performance based on the hypothesis test obtained with the calculated T value > T table (4.143 > 1.672), ? value < Sig.0.05 or (0.000 < 0.05) which means that H0 is rejected and H2 is accepted and the regression equation value Y = 3.988 + 0.375 X2, the correlation coefficient value is 0.478 meaning that both variables have a positive relationship levels. The determination value or contribution of its influence is 0.215 or 21.5%. Leadership style and work discipline simultaneously have a significant effect on employee performance based on the hypothesis test obtained with the calculated F value > F table or (27,600 > 3.16) ? value < Sig.0.05 or (0.000 < 0.05) which means H0 is rejected and H3 is accepted and the regression equation value is Y = 4.190,+ 0.332 X1, + 0.189 X2. The correlation coefficient value or level of relationship between the independent variable and the dependent variable is 0.492, meaning it has a positive level of relationship. The determination value or contribution of its influence is 0.474 or 47.4%.